Effects of social distancing on beverage consumption: An online survey with students from the interior of the country (Research, Society and Development, 2022)
The rapid pace of the spread of the coronavirus has led the government of several countries to adopt social distancing measures. This strategy generates emotional changes that modify the consumption pattern, leading to excessive intake of foods and drinks with low nutritional quality, this pattern seems to be intensified among students. Considering the vulnerability of this public, this study aims to investigate and evaluate the impacts of the pandemic on beverage consumption among technical and higher education students in the federal education network. Methodology: Survey participants answered a self-administered online questionnaire containing questions regarding beverage consumption in the previous period and during the pandemic. 106 students participated in the study. Data were analyzed using the chi-square test. Results: The findings revealed a reduction in the consumption of alcoholic beverages, artificial juice and soft drinks, in contrast, there was an increase in the consumption of fruit juices. Conclusion: Improvements were identified in the consumption of beverages during the period of social distancing among students. However, the increase in the consumption of drinks harmful to health, such as artificial juice, soft drinks and alcoholic beverages, among individuals who already had a high frequency of consumption in the period before the pandemic, may reveal the scenario of vulnerability experienced by students in Brazil.